Atypical Mycosis in Psittacine Birds: A Retrospective Study - Galosi, Livio; Falcaro, Christian; Danesi, Patrizia; Zanardello, Claudia; Berardi, Sara; Biagini, Lucia; Attili, Anna-Rita; Rossi, Giacomo (Frontiers in Veterinary Science, 2022)
A retrospective study was conducted on parrots submitted from necropsy to the Department of Veterinary Pathology, School of Biosciences and Veterinary, University of Camerino, Italy, from 2007 to 2018. From a total of 2,153 parrots examined at post-mortem, four cases were diagnosed with atypical mycosis and were considered for determination of the fungus species by PCR. A Fischer's lovebird (Agapornis fischeri), Peach-faced lovebirds (Agapornis roseicollis), and two Blue and Gold Macaws (Ara ararauna) from four different aviaries died after some days of lethargy and ruffled feathers. Records of gross necropsy and histopathological exams (H&E, PAS, and Grocott stain) were described and biomolecular analyses were carried out. No specific gross lesions were appreciated at necropsy, while histopathology evidenced a systemic mycosis in several organs, particularly in the lungs. In affected organs, broad and non-septate hyphae, suggestive of mycoses, were observed. Molecularly, Mucor racemosus (Fischer's lovebird) and M. circinelloides (Peach-faced lovebirds) were identified from formalin-fixed and paraffin-embedded (FFPE) lung and liver tissue. In addition, Alternaria alternata and Fusicladium spp. (respectively in male and female Blue and Gold macaws) were identified in FFPE tissue from several organs; whereas the role of Mucor spp. as true pathogens is well-demonstrated, and the behavior of A. alternata and Fusicladium spp. in macaws as opportunistic pathogens have been discussed. To our knowledge, this report is the first one reporting mucormycosis caused by M. racemosus and M. circinelloides in lovebirds, and A. alternata and Fusicladium spp. in macaws.